Progress in Low-Impact Processing Technologies to Deliver More Sustainable and Healthy Food Tomorrow - Marco Dalla Rosa; Santina Romani; Pietro Rocculi; Urszula Tylewicz; Silvia Tappi (Foods, 2025)
Following the debate on food processing, resulting in a negative definition of ultra-processed products, the improvement of the food system could be pursued through the co-creation of new food solutions aimed at enhancing human health and increasing safety and sustainability, in particular by using neglected foodstuff, crops or by-products, and applying mild processing technologies. The proper management of mild/non-thermal processing technologies, such as dynamic and hydrostatic high-pressure, vacuum impregnation, ultrasound, pulsed electric field and cold plasma applications, can result in a less negative effect with respect to the traditional thermal treatments, and, in some cases, the overall functionality can be improved. In many cases, these treatments can induce structural changes that improve the bioaccessibility and/or the bioavailability of bioactive compounds such as probiotic microorganisms. Moreover, non-thermal pretreatments, also combined with mild thermal drying technology, could lead to a significant reduction in the total request of energy, even when considering the energy input for their application. A selected review of results published in the last few years on those strategies is presented, considering studies carried out within the frame of different national and EU projects.